Understanding the role of family functioning, dietary adherence, and culture on glycemic control among adults with type 2 diabetes: A mediation and moderation analysis. - Halimatou Alaofè; Abidemi Okechukwu; Waliou Amoussa-Hounkpatin; Iman A Hakim; Carmelle Mizéhoun-Adissoda; Jules Gninkoun; Edward John Bedrick; John Ehiri (PLoS ONE)
Background Families and cultural contexts can impact dietary adherence and glycemic control of type 2 diabetes (T2D). Yet little is known about these relationships in Africa, where poor dietary adherence and glycemic control are prevalent. To address this gap, this study investigated whether dietary adherence mediates family functioning and glycemic control among T2D adults in Benin, West Africa. We also explored whether cultural identity affected the association between family functioning and dietary adherence. Methods A cross-sectional study of 512 T2D patients from six health centers was conducted to assess: 1) family functioning with the 12-item McMaster Family Assessment Device-General Functioning Subscale (FAD-GF); 2) dietary adherence via the Perceived Dietary Adherence Questionnaire (PDAQ); and 3) cultural identity with the 12-item Multigroup Ethnic Identity Measure (MEIM). The three-month glycemic control was determined with Glycated Hemoglobin - HbA1c. Mediation and moderation analyses were conducted using Stata's structural equation model (SEM). Results Healthy family functioning, good dietary adherence and good glycemic control rates were 56.8%, 33%, and 30.5% respectively. Path analysis showed that healthy family functioning was significantly associated with lower HbA1c levels (-0.34, 95% CI: [-0.72, -0.03]), and there was a significant indirect effect via greater dietary adherence (-0.12, 95% CI: [-0.22, -0.01]). However, cultural identity did not significantly impact the relationship between family functioning and dietary adherence. Conclusions Our study revealed that family functioning, adherence to dietary recommendations, and glycemic control are interconnected in adults with T2D. Interventions should target modifiable factors like dietary adherence and address relevant risk and resilience sources to improve glycemic control in urban African families.